Investigating EFL Students’ Perception to Speaking Performance: A Learning Experience through Hallo Application - Suhardi, Fadhilah Auliyah; Hermansyah, Sam; Isumarni, Isumarni (Journal of Language and Literature Studies, 2024)
The Hallo application, a mobile platform designed to enhance speaking skills by enabling users to connect with English speakers worldwide, has recently garnered significant attention among EFL (English as a Foreign Language) learners. This study aimed to explore EFL students' perceptions of using the Hallo application to improve their speaking performance. The research involved 15 participants from the Foreign Language Academy at Universitas Muslim Indonesia, all of whom were EFL students. A qualitative research approach was adopted, utilizing questionnaires and interviews as the primary data collection methods. The findings indicate that the students generally perceive the Hallo application as an effective tool for improving their speaking, listening, vocabulary, and pronunciation skills. They reported that the platform creates a relaxed, pressure-free environment that fosters language learning, which may contribute to greater engagement and motivation. However, the study also revealed several challenges, including the presence of excessive advertisements and encounters with inappropriate users, which could potentially hinder the overall learning experience. Based on the findings, the EFL students demonstrated a positive attitude toward the Hallo application and recognized its potential for enhancing their English-speaking performance. These results suggest that mobile applications like Hallo could be valuable tools for language learning, particularly in fostering communication practice in authentic contexts. For future research, it would be useful to explore how the integration of such applications can be further optimized to minimize user-related challenges, such as inappropriate interactions and disruptive advertisements. Additionally, investigating the long-term impact of using the Hallo application on speaking proficiency would provide more insights into its effectiveness and potential improvements.